ТАРИХИЙ ҲИКОЯЛАРДА “УМАРШАЙХ МИРЗО” ОБРАЗИНИНГ БАДИИЙ ТАЛҚИНИ - Амирқулова, З.М. (SCIENCE and SOCIETY, 2022)
This article discusses the means and features of “Umarsheyx mirzo” the artistic plot in historical stories. When writing a work on a historical topic, the author describes in detail the life of the period or the life and activities of the historical figure described by the author on the basis of historical documents, accurately depicting the historical color of this period, reflecting the language of the characters.